2004
DOI: 10.1258/095646204322637272
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis genital infection in apparently healthy adult population of Tamil Nadu, India: a population-based study

Abstract: Since the epidemiology of Chlamydia trachomatis infection in apparently healthy population has not been studied in India, a population-based study was conducted in the state of Tamil Nadu, India in order to analyse the prevalence of genital chlamydial infections in the community and to implement control programmes. A representative sample was taken from three randomly selected districts by using the 'probability proportional to size' cluster survey method. Households were the basic units of clusters. Adults ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 0 publications
1
32
1
Order By: Relevance
“…Current Indian treatment guidelines recommend VDRL and HIV testing of patients engaging in high-risk activities as part of routine STI care to be delivered through general health services. 25 Prior studies from India have shown that a large number of individuals with STIs may be harboring asymptomatic STIs, 13,26 which could contribute to the silent transmission to the community. Another study from western India found that reported symptoms had little correlation with the presence of actual infection.…”
Section: Discussionmentioning
confidence: 99%
“…Current Indian treatment guidelines recommend VDRL and HIV testing of patients engaging in high-risk activities as part of routine STI care to be delivered through general health services. 25 Prior studies from India have shown that a large number of individuals with STIs may be harboring asymptomatic STIs, 13,26 which could contribute to the silent transmission to the community. Another study from western India found that reported symptoms had little correlation with the presence of actual infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an abnormal urethral discharge and burning or painful micturition (dysuria) in men are considered suggestive of gonorrhoea and chlamydia (Adler 1998), and syndromic guidelines are used to manage symptomatic men in India (Hawkes & Santhya 2002). However, recent studies of Indian men have reported low prevalences of gonorrhoea and chlamydia (Joyee et al 2004;Lindan et al 2005), in conjunction with a high burden of reported symptoms (International Institute for Population Sciences 2001). This suggests that the syndromic guidelines for the treatment of STIs may have low specificity and costeffectiveness among symptomatic Indian men in comparison with other developing countries where the prevalence of STIs is higher (Gilson et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In India C. trachomatis -infected female patients are large in number, i.e. 30-40% [15][16][17] . Despite this high number of infected patients, there is a lacking scenario for understanding recurrent infections and their relation to clinical treatment failures.…”
Section: Discussionmentioning
confidence: 99%
“…In India, a high prevalence of genital C. trachomatis infection in women was reported earlier [15][16][17] , but studies regarding recurrent chlamydial infections and treatment failures among symptomatic women are lacking, which has an impact on reproductive health. Therefore, understanding the recurrent infections and antichlamydial drug susceptibility profile of clinical isolates from these patients is important for the development of prevention and control strategies.…”
Section: Introductionmentioning
confidence: 99%